A review of interventional schizophrenia trials registered in clinical trials registry of India - Karve, Ashwini V.; Dsilva, Renita E. (International Journal of Basic & Clinical Pharmacology, 2023)
Background: The current therapies for schizophrenia are targeted at reducing the severity of symptoms and they do not cure the disease. The research in this field is going on for many years. The present study was designed to access the current status of interventional studies conducted in schizophrenia based on studies registered in the CTRI. Methods: Interventional studies for schizophrenia registered on CTRI from 2007 to May 2022 were reviewed and analysed, using the keyword “schizophrenia”. Parameters such as number of studies, year wise distribution of the studies registered, status of the studies at the time of analysis, types of study designs, randomization, blinding, geographical distribution, type of intervention. Results: Out of 42952 studies registered with CTRI from 2007 to May 2022, 323 studies exclusively involved schizophrenia which accounts for only 0.75% of the total studies. 206 were interventional studies. Among the interventional studies 188 were randomized and 87 were blinded. Of all the interventional studies 141(68.4%) involved pharmacological interventions (Allopathy), 53 (25.7%) were non drug interventions, the rest were AYUSH. Of the 141 studies involving pharmacological interventions 28 were comparative studies with active control, 23 were addon studies, 14 were single arm efficacy and safety studies and 76 were BA/BE studies. Conclusions: The study showed a rise in schizophrenia interventional study registries in the last 5 years. However, it highlighted the need to conduct more comparative studies with active control or efficacy and safety studies rather than BA/BE studies, in order to propose better alternatives to the existing therapy.